Memperkuat Sistem Hukum Remedi Perdagangan, Melindungi Industri dalam Negeri - Nandang Sutrismo (Jurnal Hukum IUS QUIA IUSTUM, 2007)
Trade remedies, i.e. Anti Dumping, Anti Subsidy and Safeguard Action, are instruments of international trade prolicy that are the most frequently used by importing Member Countries of the World Trade Organization (WTO) to ptotect their domestic industries. However, Indonesia has been categorized as a Member Country which is the least frequently in the use of the instrument. This article recomemends that Indonesia employ the instrument more proactively in order to protect domestic industries. Parallel to this, dtrengthening the legal system of trade remedis is also urgent, since a strong lehal system either its substances, structures, and cultures, will play a crucial role on the effectiveness of the protection of domestic industries.